Kajian Kedudukan dan Peran Kabupaten Aceh Barat Daya dalam Sistem Perkotaan dan Perkonomian Nasional - Rifani Nasron (Faculty of Islamic Economics and Business at Universitas Islam Negeri Ar-Raniry in Banda Aceh, Indonesia, 2023)
Aceh Barat Daya District is part of the flagship region in Aceh Province with potential leading sectors in agriculture, plantations, and fisheries. The economic structure of Aceh Barat Daya District, which is still dominated by the primary sector (agriculture, plantations, livestock), does make this region dependent on outside areas that are directly related to the marketing flow of agricultural and plantation products. However, the productivity of this primary sector still covers the provincial scale, so it cannot be said to be a region with a national economic specialization. This study aims to determine the position and role of Southwest Aceh Regency in the urban system and the national economy. The research method used a quantitative descriptive method. The results showed that in supporting the role of Aceh Barat Daya Regency as the Aceh Andalan Region, it is a priority to develop the south-east zone seaport, namely Susoh Port in Surin Bay as the main port open to foreign trade with the main service types of containers, general cargo, liquid bulk and dry bulk of national and international scope. In addition, there is a shift in economic structure from the primary sector to the secondary and tertiary sectors in Southwest Aceh District.